Syndromic Surveillance of Norovirus Using over the Counter Sales of Medications related to Gastrointestinal Illness. Issue 4 (1st August 2006) - Edge, Victoria L; Pollari, Frank; King, Lai; Michel, Pascal; McEwen, Scott A; Wilson, Jeffrey B; Jerrett, Michael; Sockett, Paul N; Martin, S Wayne
Abstract : OBJECTIVE: To assess whether over-the-counter (OTC) sales of gastrointestinal illness (GI)-related medications are associated with temporal trends of reportable community viral, bacterial and parasitic infections. METHODS: The temporal patterns in weekly and seasonal sales of nonprescription products related to GI were compared with those of reportable viral, bacterial and parasitic infections in a Canadian province. RESULTS: Temporal patterns of OTC product sales and Norovirus activity were similar, both having highest activity in the winter months. In contrast, GI cases from both bacterial and parasitic agents were highest from late spring through to early fall. CONCLUSIONS: Nonprescription sales of antidiarrheal and antinauseant products are a good predictor of community Norovirus activity. Syndromic surveillance through monitoring of OTC product sales could be useful as an early indicator of the Norovirus season, allowing for appropriate interventions to reduce the number of infections.